Skeleton Key - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2006)
Reluctant teenage-spy Alex Rider, on a routine mission at the Wimbledon tennis championships, gets caught up in Chinese gangs, illegal nuclear weapons, and the suspect plans of his Russian host, General Sarov.